2021
DOI: 10.7759/cureus.12969
|View full text |Cite
|
Sign up to set email alerts
|

Plastics in Total Knee Replacement: Processing to Performance

Abstract: Polyethylene (PE) is the key component of total knee replacement (TKR). The wear of polyethylene, a common cause of revision surgeries, depends on multiple factors. The mechanical properties, wear characteristics, and oxidative resistance of PE can be manipulated by the techniques of processing, sterilization, and packaging methods. This article describes the making of conventional and cross-linked poly, packaging, sterilization, processing techniques, and a summary of commercially available plastics and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…The HXLPE demonstrated less osteolysis, catastrophic fracture absence, reasonable mechanical properties, and long-term survival potential in this retrospective study. Therefore, as reported by other authors [6], the HXLPE could be cost-effective in younger patients to prevent future revisions.…”
Section: Discussionsupporting
confidence: 55%
“…The HXLPE demonstrated less osteolysis, catastrophic fracture absence, reasonable mechanical properties, and long-term survival potential in this retrospective study. Therefore, as reported by other authors [6], the HXLPE could be cost-effective in younger patients to prevent future revisions.…”
Section: Discussionsupporting
confidence: 55%
“…Zaribaf et al took a different approach, devising a method to enable radiographic visualization of the entire UHMWPE insert of a TKR using Lipiodol Ultra Fluid, an iodized oil used as a clinically injectable contrast agent. ,, This was achieved by diffusing the oil into the polyethylene at an elevated temperature of 105 °C but below the melting point of the polymer (135 °C) . This method had previously been used by Oral et al to diffuse vitamin E oil into UHMWPE. ,,, Due to the load-bearing application of UHMWPE joint components, it was important that the mechanical properties of the insert remained unaltered by the diffusion of the oil. No significant changes in the mechanical and physical properties (i.e., tensile modulus, elongation at failure, ultimate tensile strength, crystallinity, and oxidative stability) were observed.…”
Section: Resultsmentioning
confidence: 99%
“… 67 This method had previously been used by Oral et al to diffuse vitamin E oil into UHMWPE. 65 , 66 , 68 , 69 Due to the load-bearing application of UHMWPE joint components, it was important that the mechanical properties of the insert remained unaltered by the diffusion of the oil. No significant changes in the mechanical and physical properties (i.e., tensile modulus, elongation at failure, ultimate tensile strength, crystallinity, and oxidative stability) were observed.…”
Section: Resultsmentioning
confidence: 99%
“…The latter uses an ultra high molecular weight polyethylene (UHMWPE) insert, 13 made from Granular-UHMWPE-Ruhrchemie (GUR) 1020 and sterilized with ethylene oxide (EtO). 14 Several smaller studies have shown good clinical results in terms of function, kinematics, and longevity of these implants. 15 - 18 Our primary aim was to assess the migration pattern of the tibial tray of the GMK Sphere using radiostereometric analysis (RSA), and to compare this with previously known limits of safe migration patterns with respect to aseptic loosening.…”
Section: Introductionmentioning
confidence: 99%